Sustainability in Library Collection Development: Introducing a Green Audit Template - McCord, David; Cassady, Samuel; Roman, Paige; Cato, Jax; Mantz, Elizabeth (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2025)
The topic of sustainability generates interest in many contemporary spheres. As partners in the publishing ecosystem, academic libraries are implicated in the push to make the content that supports teaching and research more equitable and sustainable. This paper examines the relationship between the practices of academic publishers and the sustainability goals of academic libraries related to collection management, through the lens of a Green Audit featuring a customized rubric to facilitate the assessment of the green practices of publishers. The research team assessed the environmental practices, current impact, and future commitments of publishers, with an anticipated outcome of reducing their library’s carbon footprint and advancing sustainable collection practices. Findings are drawn from an audit of 16 international academic publishers that examined material elements as well as transportation and infrastructure considerations. Audit results reveal an uneven picture of the industry, owing primarily to funding levels and staffing capacity.